Exploring Family Businesses Succession in Indonesia: The Knowledge Management Lenses - Yusuf Yeheskiel Pane; Rossalina Christanti (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This study aims to formulate knowledge management strategies within the scope of family businesses to achieve succession success. The researchers examined knowledge management practices in family businesses in Indonesia, which have a collectivistic culture and contribute to family business literature. Successor characteristics were measured using an exploratory qualitative case study approach using Likert scales and semi-structured face-to-face interviews to support data. The study's results found that successor characteristics in family businesses positively influence all succession phases, and the average values in all phases meet good criteria. Suggestions for future researchers, this family business study is limited to successful intergenerational transfer cases. It does not examine failed cases, so it needs to expand the sample to a wider range of family businesses undergoing transition.